Characterization of the genetic and regulatory networks associated with sugar and acid metabolism in apples via an integrated strategy - Shen, Fei; Hu, Chenyang; Huang, Xin; Wu, Ruigang; Luo, Shuzhen; Xu, Chengnan; Zhang, Hong; Wang, Xuan; Zhao, Jirong (Frontiers in Plant Science, 2022)
Sugar and acid influence the taste of apple fruits substantially. However, the underlying genetic and regulatory network remains elusive. To fully decipher the genetic basis of the accumulation of sugar and acid in apple fruits, we adopted the integrated strategy including Time-course RNA-seq, QTL mapping, and whole-genome sequencing toward two typical cultivars ('HanFu' and 'Huahong') with a distinct flavor. Whole genome sequencing indicated a mass of genetic variations between the two cultivars, which provided a range of genetic basis for the distinct phenotypes. The constructed co-expression networks indicated the existence of the intra-relationships among the accumulation of different types of metabolites and also revealed critical regulatory nodes associated with the accumulation of sugars and acids, e.g., MdEF2, MdPILS5, and MdGUN8. Additionally, we conducted the QTL mapping using the high-density genetic map and identified a series of QTLs and functional genes underly the vital traits including sugars and acids. Collectively, the observation and methodology would provide an important reference for the studies about apple favors.